Factors Affecting Financial Distress in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2016–2020 - Sitanggang, Tina Novianti; Cindy, Cindy; Hansen, Hansen; Jesslyn, Jesslyn; Cynthia, Cynthia (Budapest International Research and Critics University, 2021)
This study was conducted to determine the factors affecting financial distress in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2016–2020. The data used is sourced from the company's financial statements on the Indonesia Stock Exchange, and the sample has been selected based on predetermined criteria. The population in this study are all Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2016–2020 totaling 30 companies, with purposive sampling method, the sample received is 12 companies. From this research, it can be seen that sales growth and working capital turnover partially effect financial distress significantly. Institutional ownership and debt to equity ratio have an insignificant effect on financial distress. All variables have a significant effect on financial distress simultaneously.